Removal of Methylene Blue in Aqueous Solution with Modified Biomass from Forest Residues (quercus Alba) - Angel Villabona-Ortiz; Rodrigo Ortega-Toro; Adriana Herrera-Barros; Leidy Castillo-Solano; Luis Sierra-Payares (Chemical Engineering Transactions, 2025)
Biochar is a product derived from the decomposition of biomass, and its physicochemical characteristics are closely linked to its source and the method of combustion employed. Key properties of biochar include its surface area, the development of macro and micropores, and the presence of various functional groups. This study aimed to synthesize activated carbons (AC) from Quercus alba sawdust, modified with phosphoric acid and urea at different concentrations (1, 3, and 6 M), identifying through physicochemical characterization its possible use as an adsorbent for the cationic dye methylene blue (MB). The prepared bio-based adsorbents were physiochemically characterized by Fourier-Transform Infrared Spectroscopy (FTIR), mechanical tests to determine porosity, pore distribution, and adsorption capacity by determining the methylene blue index. The biochar activated and functionalized with urea at a concentration of 6 M (C 6M) presented the best characteristics for the adsorption of dyes, the pH at the zero-loading point (pHpzc) was 6.1, and the methylene blue index corresponded to a qe of 16.77 mg/g. The FTIR spectra showed the changes that occur with increasing urea concentration. Based on their characteristics, it can be indicated that bioadsorbents prepared from Quercus alba sawdust can be used for the adsorption of azo dyes, obtaining a high percentage of removal.